MASSIVE OPEN ONLAYN COURSES - Babadjanova Guzal Bakhtiyorovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
ABSTRACT: In this article, we got acquainted with the advantages, disadvantages and opportunities of public open online courses. And will also have some understanding of the types and functions of MOOC platforms.